PENYULUHAN KESEHATAN HEWAN DI DESA CAMPLONG II, KECAMATAN FATULEU, KABUPATEN KUPANG, PROVINSI NUSA TENGGARA TIMUR - Tangkonda, Elisabet; Kallau, Novalino Harold Geoffrey; Gelolodo, Maria Aega; Loe, Fhady Risckhy; Jampur, Sesarius Wahyu Pagung (Jurnal Media Tropika, 2023)
The outbreak of Foot and Mouth Disease (FMD) and African Swine Fever (ASF) in Indonesia needs to be counteracted by providing education and increasing awareness to the farming community about the importance of animal health and its impact on the economy and human health. Apart from that, the public also needs to be educated about the transmission and prevention of FMD, which is still free in NTT, and ASF disease, which is currently being eradicated. Members of the Telekomunit Farmers Group, the Sanam Tuan Farmers Group, the Sabu Bani Farmers Group, and the Setetes Madu Farmers Group in Camplong II Village, Fatuleu District, Kupang Regency, Nusa Province East Southeast are being helped through communication and education as part of this service activity. The goal is to make them more aware of the threat of PMK and ASF. In this activity, the community was also educated about rabies, which has become an epidemic in TTS, one of the areas on the island of Timor, and has been designated as an extraordinary rabies event.